Efficiency of two contrasted marine protected areas (MPA) in West Africa over a decade of fishing closure. (1st September 2021) - Thiaw, Modou; Gascuel, Didier; Sadio, Oumar; Ndour, Ismaïla; Diadhiou, Hamet Diaw; Kantoussan, Justin; Faye, Saliou; Thiam, Modou; Meissa, Beyah; Brehmer, Patrice
Abstract: Using trophodynamic models, the present study evaluated how a decade fishing closure inside and outside two marine protected areas (MPAs) in Senegal has influenced on the ecosystem trophic network. Scientific surveys in the Bamboung MPA (68 km 2, mangrove) were conducted since 2003, one year before fishery closure. The resulting dataset was used to generate a time series of abundance indices, and Ecopath mass-balanced models were constructed for the 2003, 2008–2012, and 2015–2016 periods (one fished and two unfished periods, respectively). These three Bamboung MPA models were subsequently used to evaluate the effects of fishing closure. Based on the biomass trophic spectrum of the 2015–2016 model, the trophic structure of the Bamboung MPA was compared to that constructed in the same period of an area that was still fished (Bolong de Sankago). Using a model based on ecosystem trophic levels (EcoTroph) we simulated fishery activity in the Bamboung MPA from 2008, to assess possible poaching in the MPA. Then, the effect of fishing closure was also evaluated on the continental shelf for the Joal-Fadiouth MPA (174 km 2 ; sandy coast/mangrove), and comparing the trophic structure inside and outside of this second MPA. The results showed that the Bamboung MPA had high biomass, especially for higher trophic level species. After a decade of fishing closure, a 2-fold increase in predator biomass and a 1.5-fold decrease in prey biomass was recorded. The models showed that poaching effects exist both studied MPA. So official fishing closure had after a decade a lower effect in both MPAs. For the Joal-Fadiouth MPA, low-mobility species had high biomass, suggesting that high habitat diversity and fishery closure had a positive effect. However, the biomass of large species from high-trophic-levels was still low inside this MPA. The obtained results could serve as a reference for future studies in this MPA. In conclusion, fishery closure increased the total biomass in the MPAs over the medium and long-term; however, the trophic network might also be modified by high natural variability in the annual recruitment of some stocks. Graphical abstract: Image 1 Highlights: After a decade of fishing closure, a 2-fold increase in predator biomass and a 1.5-fold decrease in prey biomass was recorded in the Bamboung MPA. Due to poaching effects, the official fishing closure had after a decade a lower effect in both MPAs. For the Joal-Fadiouth MPA, low-mobility species had high biomass, suggesting that high habitat diversity and fishery closure had a positive effect. The fishery closure increased the total biomass in the MPAs over the medium and long-term. However, the trophic network might also be modified by high natural variability in the annual recruitment of some stocks.